FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN NON KEUANGAN DI BURSA EFEK INDONESIA - Gabriella Rachel Sugandi; Frestin Chrisnanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to analyze the effect of company size, company age, capital structure, financial performance, profitability, liquidity, dividend policy, and managerial ownership toward firm value. This research used 50 listed non-financial companies in Indonesia Stock Exchange in period 2018 to 2020. The method of sampling used purposive sampling and this study used multiple regression analysis. The results of this study found that company age, financial performance, and managerial ownership have influence to firm value. While the company age, capital structure, profitability, liquidity, and dividend policy have no influence to firm value